2020
DOI: 10.1177/1420326x20938831
|View full text |Cite
|
Sign up to set email alerts
|

Biocontamination of surfaces in controlled environment rooms: The influence of environmental parameters and the design of the air conditioning system

Abstract: This research aims to evaluate the relationship between the environmental and design parameters of the air conditioning system, and the presence of colony-forming units (CFUs) of bacteria on surfaces. This retrospective study was carried out in controlled environment rooms in 12 hospitals in Spain, as part of a periodic environmental biosecurity assessment programme. Between 2010 and 2017, a total amount of 1027 samples were collected from floors and 861 from hand contact surfaces (HCSs), and the environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Temperature and relative humidity have a significant influence on the presence of microorganisms in the air and on surfaces (Eames et al, 2009; Fu Shaw et al, 2018; Sabuco-Tébar et al, 2020; Shajahan et al, 2019). Humidity, nutrients, and temperature are the most important factors that influence the growth of airborne fungi (Haleem Khan & Mohan Karuppayil, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Temperature and relative humidity have a significant influence on the presence of microorganisms in the air and on surfaces (Eames et al, 2009; Fu Shaw et al, 2018; Sabuco-Tébar et al, 2020; Shajahan et al, 2019). Humidity, nutrients, and temperature are the most important factors that influence the growth of airborne fungi (Haleem Khan & Mohan Karuppayil, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Although the influence of the position of the HEPA filter on the presence of fungi in the air has been demonstrated, other factors also influence the level of containment of the rooms (ACH and differential pressure). These parameters contribute to the maintenance of environmental biosafety by preventing the entry of microorganisms from adjacent spaces, by renewing the air, and by maintaining the cleanliness of the air and surfaces (Sabuco-Tébar et al, 2020; Sehulster et al, 2003). UNE 171340 (2020) establishes 15 ACH for very high risk, high risk, and medium risk rooms (type of the rooms analyzed in this research); 10 ACH for low risk; and five ACH for minimal risk rooms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant differences were reported in temperature and relative humidity between rooms. Parameters such as temperature and relative humidity influence the growth and survival of microorganisms (Sabuco-Tébar et al, 2020; Sehulster et al, 2003; Wagenvoort et al, 1993). A review concluded that fungi and bacteria had different survival conditions regarding temperature and relative humidity; temperatures above about 24°C (75.2°F) decrease the air survival of gram-negative, gram-positive, and intracellular bacteria, while fungi are more resistant in extreme environmental conditions and survive in higher temperatures (Tang, 2009).…”
Section: Discussionmentioning
confidence: 99%